Pengembangan Evaluasi Paket Instruksi Renang Umum Korps Marinir AAL - Bambang Eko Saputro; Sumarwoto Sumarwoto; Agus Salim; Budi Santoso (Saintek: Jurnal Sains Teknologi dan Profesi Akademi Angkatan Laut, 2023)
This study examines the swimming instruction package, focusing on the essential factors to improve the quality of the Marine Corps Cadets General Swimming Instruction Package to facilitate the understanding of AAL Marine Corps Cadets in completing their final assignment. The sub-aspects being investigated included aspects of the feasibility of the contents of the Public Swimming PI material, the language aspects of the Public Swimming instruction packs, material presentation of Public Swimming instruction packs, and aspects of graphic design of the Public Swimming instruction. Our research design contained steps of analysis, design, evaluation, and revision, while the data analysis was carried out using descriptive qualitative. Based on all the analysis results, the average score for each aspect is a) the design attains an average value of 95 percent; b) the content attains an average value of 94 percent; c) individual exercise attains an average value of 94 percent; d) small group exercise attained an average value of 91.8 percent; and e) field trial attains average value of 90.8 percent. Thus, the total average score is 93.12 percent. Penelitian ini mengkaji paket instruksi dengan memperhatikan faktor-faktor yang perlu diperbaiki untuk meningkatkan kualitas Paket Instruksi (PI) renang umum taruna Korps Marinir agar dapat membantu memudahkan pemahaman para taruna dalam menyelesaikan tugas akhir. Adapun sub aspek yang diteliti meliputi aspek kelayakan isi materi, aspek kebahasaan, aspek penyajian dan aspek desain grafis dari PI renang umum. Proses penelitian ini menerapkan design research meliputi langkah-langkah analisis, perancangan, evaluasi, dan revisi, sedangkan teknik analisis data dilakukan menggunakan deskriptif kualitatif. Berdasarkan seluruh uji coba yang penulis laksanakan maka nilai rata- rata hasil dari uji coba tersebut: a) uji coba desain 95 persen; b) uji coba isi 94 persen; c)uji coba perorangan 94 persen; d) uji coba kelompok kecil 91,8 persen; dan e) uji coba lapangan 90,8 persen. Sehingga nilai rata-rata keseluruhan adalah 93,12 persen.